UNDERSTAND THE GLOBAL ECONOMIC CRISIS: A TEXT SUMMARIZATION APPROACH. Issue 2 (6th June 2013) - Liu, Shuhua; Favre, Benoit
SUMMARY Economic crises are significant threats to macroeconomic stability. They can incur large costs and bring devastating effects on economies, with the effects often spilling over into other economies. Since 2007 we have witnessed the most severe and widely spread economic crisis since the Great Depression of the 1930s. In the meantime, a huge amount of ongoing media coverage, reporting, analysis and debate concerning the global economic crisis has been generated. In this study we explore the possibilities of applying text summarization tools to learn from text documents the various discussions surrounding the global economic crisis. Included in our analysis are blog posts and articles of highly influential economists, as well as official speeches and publications of government organizations. The ICSI‐ILP extractive summarizer is applied in a large number of experiments, and the summary outputs are manually examined and evaluated. The results provide us with insights into the potential and limitations of state‐of‐the‐art summarization systems when used to help us quickly learn and digest large amounts of textual information. The results also suggest different ways to break the limitations of text summarization technology. Copyright © 2013 John Wiley & Sons, Ltd.